Innovation in Nano Meniran Extract Feed as a Solution for Odor Reduction and Productivity in Muscovy Ducks: Inovasi Pakan Nano Ekstrak Meniran sebagai Solusi Reduksi Bau dan Produktivitas Bebek Entok - Sabdoningrum, Emy Koestanti; Hidanah, Sri; Hendarti, Gracia Angelina; Warsito, Sunaryo Hadi; Lamid, Mirni; Al Arif, Mohammad Anam; Lokapirnasari, Widya Paramita; Widodo, Oky Setyo; Rosyada, Zulfi Nur Amrina; Soeharsono, Soeharsono; Hernanda, Ary Setya; Fitriyah, Hadiah (Indonesian Journal of Innovation Studies, 2025)
AbstractGeneral background: Small-scale poultry farming in rural Indonesia faces challenges of low productivity and environmental pollution due to traditional feeding practices. Specific background: In Sepande Village, Sidoarjo, Muscovy duck (Cairina moschata) farmers struggle with suboptimal growth performance and unpleasant waste odor, exacerbated by high feed costs. Knowledge gap: While local feed resources and herbal additives have been studied, the integration of nano herbal technology into fermented feed for Muscovy ducks has not been explored. Aims: This study aimed to evaluate the effectiveness of nano-extract meniran (Phyllanthus niruri) as a feed additive in fermented pellet feed to enhance productivity and reduce waste odor. Results: Application of 1–3% nano meniran in duck feed led to a 50% increase in body weight (from 1.5 kg to 2.27–3.0 kg within three months), a 30% increase in farmer income, and a 93.75% improvement in regular odor-control practices, while significantly reducing waste odor intensity. Novelty: This is the first integration of nanotechnology-based herbal additives with fermented local feed formulations for Muscovy ducks. Implications: The innovation supports food security, farmer welfare, and sustainable livestock management, offering an eco-friendly model for poultry production in developing regions. Highlight: Nano meniran feed boosts duck growth by up to 50%. Odor reduction improves farm environment and sustainability. Farmers’ income increases by around 30%. Keywords: Muscovy Duck, Nano-Extract Meniran, Fermented Feed, Productivity, Waste Odor Reduction